2012
DOI: 10.1111/j.1442-2042.2012.03165.x
|View full text |Cite
|
Sign up to set email alerts
|

α1‐blocker tamsulosin as initial treatment for patients with benign prostatic hyperplasia: 5‐year outcome analysis of a prospective multicenter study

Abstract: Abbreviations & AcronymsObjective: To comprehensively analyze the 5-year outcomes of tamsulosin treatment for patients with benign prostatic hyperplasia. Methods: Tamsulosin (0.2 mg/day) was given to 112 patients who had International Prostate Symptom Scores Ն8. They were prospectively followed for 5 years with periodic evaluation. If tamsulosin had to be discontinued, the reason was determined. Treatment failure was considered in the case of disease progression (postvoid residual urine volume Ն200 mL, acute u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 28 publications
1
44
0
2
Order By: Relevance
“…Alpha-1 blockers such as tamsulosin are routinely used for benign prostatic hypertrophy and UR [11]. They work by relaxing the detrusor muscles and facilitating bladder emptying.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-1 blockers such as tamsulosin are routinely used for benign prostatic hypertrophy and UR [11]. They work by relaxing the detrusor muscles and facilitating bladder emptying.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the continuation rates with α 1-adrenoceptor antagonists for LUTS/BPH have been prospectively studied. Masumori et al reported that the continuation rates for tamsulosin at 5 years and for naftopidil at 3 years were 30.4% and 21.4%, respectively [14, 15]. Yamanishi et al reported that the continuation rate for silodosin at 6 years was 25% [13].…”
Section: Discussionmentioning
confidence: 99%
“…Since 5 α -reductase inhibitors have been approved in Japan since 2009, all patients enrolled between 2007 and 2009 in this study were treated with silodosin monotherapy (4 mg) twice daily as its routine prescription in Japan. The scheduled number of the enrolled patients was 100 according to previous similar studies [14, 15]. Most patients were prescribed silodosin at one- or two-months intervals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…But they are not always effective for treating symptoms of NAC [7]. If patients have strong concomitant symptoms of OAB, strategy of substitution of a1-blocker with anti-cholinergic agent, additional simultaneous prescription of anti-muscarinic drug and substitution of a1-blocker with other drug of the same group is used [8,9]. Sixth International Consultation On New Developments in Prostate Cancer and Prostate Diseases [10] and some special studies [11] adopted recommendations on combined administration of a1blocker and anti-cholinergic drugs as a rational therapy for obstruction of urethra in prostatic gland area associated with symptoms of OAB.…”
Section: Introductionmentioning
confidence: 99%